Peningkatan Kandungan Kalium Urin Setelah Pemberian Ekstrak Sari Buah Belimbing Manis (Averrhoa carambola) (THE INCREASE OF POTASSIUM URINE CONTENT AFTER ADMINSTRATION OF CARAMBOLA (AVERRHOA CARAMBOLA) FRUIT JUICE EXTRACT) - Panjaitan, Ruqiah Ganda Putri; Bintang, Maria (Jurnal Veteriner; Vol 15 No 1 (2014), 2014)
Carambola (Averrhoa carambola L.) has been used as medicinal plant. This research has beenconducted to study the potential diuretic of fruit juice carambola extract on male rats. Diuretic activitywas tested by using Cumming’s method. The treatment was administered only once, and the urine up to 24hours after treatment was collected. The result shows that the administration of 1.6 mL/100 g body weightof fruit juice carambola extract resulted in lower urine volume compared to the without treatment orklortalidon at dose 0.315 mg/100 body weight (p>0.05). Furthermore, Na+ content in treatment rats’ wasurine lower compared to the without treatment or klortalidon (p<0.05). in contrast, high content of K+ wasobserveb in treatment  rast’ urine compared to the without treatment or klortalidon (p> 0.05). It is concludedthat the administration of carambola fruit juice extract may increase K+ content in urine and produce moreconcentrated urine. The mechanism of action, however, remains need to be proven, further.
Keywords: Averrhoa carambola, fruit juice extract, potassium content in urine